Analysis of Production Functions and Efficiency of Corn at Patean District Kendal Regency (Universitas Negeri Semarang, 2015)
Food is the major need for human to survive. Corn is one of the most important food crops in the world after wheat and rice. Besides, corn is a source of carbohydrates and can also be an alternative food source. In fact, the world demand for corn to meet the need of food and cattle industry has increased every year as well as at the national level. This is due to not only the growth of population, but also the food and farm industry. The growth of corn farm increased rapidly in the last three years in Patean subdistrict, Kendal regency. However, the productivity was still low reaching only 4.57 tons/ha. This condition is interesting to review especially on the anlysis of production function and the efficiency of maize farming in the area. The aim of this reseach was to analyze the producton function and efficiency of maize farming. This study used Frontier Analysis approach.